Exporation of Microeconomics - Sexton, Robert L. (Singapore, 2012)
Exploration of Microeconomics, was wirtten to not only be a student-friendly textbook, but one that was relevant, one that focused on those few principles and application that demonstrate the enormous breadth of economics to everyday life. Thist text is lively, motivating, and exciting, and it helps students relate economics to their world.
Keywords: Microeconomics